KEPENTINGAN INDONESIA MENGGUGAT UNI EROPA TERKAIT MINYAK SAWIT DAN BIOFUEL DARI TANAMAN KELAPA SAWIT MELALUI WORLD TRADE ORGANIZATION (WTO) PADA KODE KASUS DS593 - Bayti, Tiara Nur; Iskandar, Irwan (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2026)
This research analyzes the national interests underpinning Indonesia's decision to file a lawsuit against the European Union (EU) at the World Trade Organization (WTO) through dispute DS593. The lawsuit was a response to the EU's Renewable Energy Directive II (RED II) policy, which classifies palm oil as a high-risk crop (High ILUC-Risk) and mandates a gradual phase-out until 2030. This study employs a qualitative approach with a descriptive-analytical method. Data collection techniques were conducted through literature reviews and document analysis, encompassing the RED II policy and the DS593 dispute filings. The research utilizes the perspective of Institutional Liberalism, the Nation-State Level of Analysis, and Donald E. Nuechterlein’s Concept of National Interest to analyze the dimensions of the interests pursued by Indonesia. The results indicate that the RED II policy is a form of EU